G2: A Graph Processing System for Diagnosing Distributed Systems - Guo, Zhenyu; Zhou, Dong; Lin, Haoxiang; Yang, Mao; Long, Fan; Deng, Chaoqiang; Liu, Changshu; Zhou, Lidong (USENIX ATC 2011, 2011)
G2 is a graph processing system for diagnosing distributed systems. It works on execution graphs that model runtime events and their correlations in distributed systems. In G2, a diagnosis process involves a series of queries, expressed in a high-level declarative language that supports both relational and graph-based operators. Each query is compiled into a distributed execution. G2’s execution engine supports both parallel relational data processing and iterative graph traversal. Execution graphs in G2 tend to have long paths and are in structure distinctly different from other largescale graphs, such as social or web graphs. Tailored for execution graphs and graph traversal operations on those graphs, G2’s graph engine distinguishes itself by embracing batched asynchronous iterations that allows for better parallelism without barriers, and by enabling partition-level states and aggregation. We have applied G2 to diagnosis of distributed systems such as Berkeley DB, SCOPE/Dryad, and G2 itself to validate its effectiveness. When co-deployed on a 60-machine cluster, G2’s execution engine can handle execution graphs with millions of vertices and edges; for instance, using a query in G2, we traverse, filter, and summarize a 130 million-vertex graph into a 12 thousandvertex graph within 268 seconds on 60 machines. The use of an asynchronous model and a partition-level interface delivered a 66% reduction in response time when applied to queries in our diagnosis tasks.
The 2011 USENIX Annual Technical Conference